Inheritance of the Bantu/Benin haplotype causes less severe hemolytic and oxidative stress in sickle cell anemia patients treated with hydroxycarbamide - Okumura, Jéssika V. [UNESP]; Silva, Danilo G.H. [UNESP]; Torres, Lidiane S [UNESP]; Belini-Junior, Edis [UNESP]; Barberino, Willian M [UNESP]; Oliveira, Renan G [UNESP]; Carrocini, Gisele C.S. [UNESP]; Gelaleti, Gabriela B; Lobo, Clarisse L.C.; Bonini-Domingos, Claudia R [UNESP] (Springer Nature, 2016)
Beta S-globin gene cluster haplotypes (β S -haplotypes) can modulate the response to hydroxycarbamide (HC) treatment in sickle cell anemia (SCA) patients. In Brazil, the most common haplotypes are Bantu and Benin, and both confer a poor prognosis for patients when untreated with HC. We evaluated oxidative and hemolytic biomarkers in 48 SCA patients undergoing HC treatment separated in three subgroups: Bantu/Bantu, Bantu/Benin and Benin/Benin haplotype. On the basis of reduced haptoglobin (HP) levels, patients with Bantu/Bantu haplotypes had 3.0% higher hemolysis degree when compared with those with Bantu/Benin haplotypes (P=0.01). The Benin/Benin patients had 53.6% greater lipid peroxidation index than the Bantu/Bantu patients (P=0.01) because of evaluated thiobarbituric acid reactive species levels. The Bantu/Benin subgroup had intermediate levels of hemolytic and oxidative stress markers compared with the homozygous subgroups. Through strict inclusion criteria adopted, as well as consolidated and well-described hemolytic and the oxidative parameters evaluated, we suggest a haplotype-interaction response to HC treatment mediated by a 'balance' between the genetic factors of each haplotype studied.